Manufacturing method of optical component and optical component

By coating YAG single crystals with Si and divalent ion-containing thin films and heat treating them, the method addresses voids and thermal conductivity issues, improving the laser damage threshold for high-power lasers.

JP2025001175AActive Publication Date: 2025-01-08SHINKOSHA
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2023100627
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-20
Publication Date
2025-01-08
Estimated Expiration
2043-06-20

AI Technical Summary

Technical Problem

YAG single crystals and polycrystalline YAG ceramics used in solid-state lasers suffer from low laser damage threshold, low thermal conductivity, and voids at the bonding interface, which are problematic for high-power applications.

Method used

A method involving mirror-polishing YAG single crystals, coating them with a thin film containing Si and divalent ions like Mg and Ca, and performing heat treatment under controlled conditions to reduce voids at the bonding interface.

Benefits of technology

The method results in a bonded YAG single crystal structure with minimal voids, enhancing thermal conductivity and laser damage threshold, suitable for high-power laser applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025001175000001_ABST
    Figure 2025001175000001_ABST
Patent Text Reader

Abstract

To provide a manufacturing method of an optical component using a YAG single crystal with extremely few voids at the bonding interface, and an optical component.SOLUTION: The surfaces of a doped YAG single crystal and the undoped YAG single crystal are mirror-polished, and at least one of the surfaces of the doped YAG single crystal and the undoped YAG single crystal is coated with a thin oxide film containing Si and an element that is to become a divalent ion. The surfaces of the doped YAG single crystal and the undoped YAG single crystal are then brought into contact with each other and heat-treated.SELECTED DRAWING: Figure 5
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for manufacturing optical components such as laser gain media and fluorescent light-emitting devices made of YAG (yttrium aluminum garnet) single crystals, and to the optical components. [Background technology]

[0002] In fields such as laser processing, there is a demand for small, high-power, high-beam quality lasers. Recently, solid-state lasers using laser diodes (LDs) as excitation light sources have become widespread. In particular, yttrium aluminum garnet (hereinafter referred to as "YAG") crystals doped with neodymium (Nd) or ytterbium (Yb) are increasingly being used as solid-state laser materials.

[0003] In order to realize a high-power output laser beam from a solid-state laser, the dissipation of heat generated in the solid, which is the laser gain material, is a major problem. As a method for effectively dispersing localized heat generation, it has been proposed to join a laser crystal doped with an optically active substance to an undoped crystal, and the diffusion bonding method and direct bonding method have been devised (Patent Document 1).

[0004] Research into the structure of the laser medium has also progressed, and a method using a disk-shaped laser gain material is known. By forming the laser gain material into a thin disk shape, the light receiving surface of the external excitation light can be made large, and uniform cooling can be achieved over the entire disk surface. Among these, the reflective (active mirror) structure has attracted attention because it allows cooling by a heat sink or fluid by applying a reflective film to one surface of the thin film disk. Normally, active mirror structures improve mechanical strength and heat dissipation by joining a thin film disk doped with an optically active substance to a material not doped with an optically active substance (Patent Document 2).

[0005] As a means for cooling the laser medium, many techniques have been proposed for bonding with a heat transfer member. For example, Patent Document 3 discloses a technique in which the bonding surface is treated with oxygen plasma, and then irradiated with an atomic beam of an inert gas to perform surface activation bonding. The technique disclosed therein shows that it is also possible to bond the YAG laser medium, which is an oxide, to sapphire, which is an oxide and serves as a heat transfer member. In addition, among these, it is shown that when the laser medium is polycrystalline, the laser medium is easily destroyed by electric field concentration occurring near the interface between the laser medium and space, and that the optical damage threshold is lower than that of a single crystal, and that as a countermeasure, it is possible to increase the optical damage threshold by surface activation bonding a transparent single crystal to the end face (Patent Document 3,

[0027] ).

[0006] Various bonding techniques have also been disclosed in the field of electronic components. For example, Patent Document 4 proposes an atomic diffusion bonding method in which an amorphous oxide thin film is formed in a vacuum and chemical bonds are generated at the bonding interface through atomic diffusion. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] Patent No. 4374415 [Patent Document 2] Patent No. 5330801 [Patent Document 3] Patent No. 6245587 [Patent Document 4] Patent No. 7131778 Summary of the Invention [Problem to be solved by the invention]

[0008] YAG single crystals and polycrystalline YAG ceramics are used as media for solid-state lasers. Although YAG ceramics have the advantage of being easy to manufacture in large sizes and relatively inexpensively, it is preferable to use YAG single crystals for high-power lasers because of the presence of grain boundaries, the laser damage threshold is low, and the thermal conductivity is lower than that of single crystals, especially at low temperatures.

[0009] In addition, as a technique for joining a laser medium and a heat dissipating member, in the case of a polycrystalline body, a method has been proposed in which the raw powder of the laser medium and the heat dissipating material are brought into contact and sintered at the same time, but in the case of a laser medium using a YAG single crystal, it is necessary to process and join a YAG single crystal doped with an optically active substance and an undoped YAG single crystal after crystal growth. For this reason, it is necessary to join the joining interface by polishing it to a flat mirror finish, but voids may remain at the interface after joining. Since it is thought that these tiny voids may have an effect on high-power lasers, a joined single crystal without voids at the joining interface is desired.

[0010] The present invention has been made in consideration of the above problems, and an object of the present invention is to provide a method for manufacturing an optical component using a YAG single crystal with extremely few voids at the bonding interface, and to provide the optical component. [Means for solving the problem]

[0011] In order to achieve the above object, a method for producing an optical component according to the present invention comprises mirror-polishing a surface of a doped YAG single crystal, which is an yttrium-aluminum-garnet single crystal doped with an optically active substance, and a surface of an undoped YAG single crystal, which is an yttrium-aluminum-garnet single crystal not doped with an optically active substance, coating at least one of the surfaces of the doped YAG single crystal and the undoped YAG single crystal with a thin film containing Si, and then bringing the surfaces of the doped YAG single crystal into contact with each other and subjecting them to a heat treatment.

[0012] The method for producing an optical component according to the present invention is characterized in that the thin film is an oxide thin film containing an element that becomes a divalent ion.

[0013] The method for manufacturing an optical component according to the present invention is characterized in that the heat treatment turns the junction between the surface of the doped YAG single crystal and the surface of the doped YAG single crystal into an oxide thin film containing Ca and Mg.

[0014] The method for producing an optical component according to the present invention is characterized in that, in the heat treatment, the heat treatment is performed in the air at 1200° C. or more and 1600° C. or less, and then hot isostatic pressing is performed in an atmosphere containing O 2 .

[0015] The optical component according to the present invention is an optical component in which a surface of a doped YAG single crystal, which is an yttrium aluminum garnet single crystal doped with an optically active substance, is bonded to a surface of an undoped YAG single crystal, which is an yttrium aluminum garnet single crystal not doped with an optically active substance, and is characterized in having a thin film containing Si at the bonded portion between the doped YAG single crystal and the undoped YAG single crystal.

[0016] The optical component according to the present invention is characterized in that the thin film is an oxide thin film containing an element that becomes a divalent ion.

[0017] The optical component according to the present invention is characterized in that the oxide thin film contains both Ca and Mg as the elements that become divalent ions.

[0018] In the present invention, it has been found that, in a method for producing a laser medium in which a YAG single crystal doped with an optically active substance such as Nd, Yb, Ce (doped YAG single crystal) is bonded to an undoped YAG single crystal (undoped YAG single crystal), voids at the bonded interface can be reduced by the following means: That is, it has been found that a laser medium with fewer voids at the bonded interface can be produced by mirror-polishing the bonded surfaces of the doped YAG single crystal and the undoped YAG single crystal, coating at least one of the surfaces with a thin film containing Si by a method such as sputtering, and then bonding the bonded surfaces together and subjecting them to heat treatment. By coating the YAG single crystal with a thin film containing Si, Si diffuses into the YAG single crystal as ions during heat treatment, activating the movement of atoms near the bonding interface and making it possible to reduce voids at the interface.

[0019] If the thin film containing Si is Si, it will be oxidized during heat treatment and Si will ionize and diffuse. Therefore, although a Si film can also reduce voids at the bonding interface, it is preferable to coat it with a Si oxide film since it will be oxidized during heat treatment. In the present invention, the composition of the thin film containing Si can be an oxide composition containing at least one selected from divalent ions such as Mg, Ca, Fe, Mn, etc., and tetravalent ions such as Si. Si diffuses by substituting trivalent Y or Al ions in the YAG crystal with tetravalent ions, and it is believed that the coexistence of divalent Mg, Ca, etc. compensates for the charge, making the substitution easier, facilitating diffusion, and reducing voids. These divalent ions and Si diffuse into the YAG crystal to form a garnet structure, which is believed to reduce optically inhomogeneous phases.

[0020] Furthermore, by using an oxide containing Mg, Ca, and Si in the thin film, it is possible to reduce voids. The coexistence of Mg and Ca is thought to promote diffusion near the interface, and the presence of an amorphous phase promotes the elimination of voids.

[0021] In the present invention, the heat treatment is preferably performed in air at a temperature of 1200°C or higher and 1600°C or lower. Since oxygen deficiency may occur when the YAG single crystal is heat-treated in a reducing atmosphere, it is preferable to heat-treat the YAG single crystal in an oxidizing atmosphere, that is, in air. The heat treatment temperature is lower than 1200°C because ions of Si, Mg, Ca, etc. do not diffuse sufficiently, and higher than 1600°C because voids may grow. Furthermore, it is more preferable to perform hot isostatic pressing (HIP) treatment after the heat treatment in air. The HIP treatment is preferably performed in an atmosphere that prevents the reduction of YAG, and may be performed in an atmosphere containing O2, for example, an Ar+O2 atmosphere. The pressure and temperature may be normally used, for example, 1500°C and 200 MPa. By performing the HIP treatment, the voids at the bonding interface are further reduced. Effect of the Invention

[0022] The present invention makes it possible to provide optical components such as laser medium cemented bodies made of single crystal materials with no voids at the cemented interface. [Brief description of the drawings]

[0023] [Figure 1] SEM photographs of fracture surfaces of joints in comparative examples compared to the embodiment of the present invention. [Diagram 2] SEM photograph of a fracture surface of a bonded body of an optical component according to a first embodiment of the present invention, which is manufactured by a manufacturing method for an optical component according to an embodiment of the present invention. [Diagram 3] SEM photograph of a fracture surface of a bonded body of Example 2 of an optical component manufactured by a manufacturing method for an optical component according to an embodiment of the present invention. [Figure 4] SEM photograph of a fracture surface of a bonded body of Example 3 of an optical component manufactured by a manufacturing method for an optical component according to an embodiment of the present invention. [Diagram 5] SEM photograph of a fracture surface of a bonded body of Example 4 of an optical component manufactured by a manufacturing method for an optical component according to an embodiment of the present invention. [Figure 6]SEM photograph of a fracture surface of a bonded body of Example 5 of an optical component manufactured by a manufacturing method for an optical component according to an embodiment of the present invention. [Figure 7] SEM photograph of a fracture surface of a bonded body of Example 6 of an optical component manufactured by a manufacturing method for an optical component according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0024] Hereinafter, an embodiment of the present invention will be described in detail. As a medium for a solid-state laser, a joint of a Nd:YAG single crystal or a Yb:YAG single crystal and an undoped YAG single crystal is useful. These YAG single crystals can be grown by methods such as the Czochralski method. However, single crystals grown by the Czochralski method are expensive to manufacture because they use precious metals such as iridium in the crucible, making it difficult to grow large crystals. However, the inventors have developed a technology for growing large crystals without using an iridium crucible (Patent Publication No. 2023-056860, Patent Publication No. 2023-056861), making it possible to manufacture large YAG single crystals relatively inexpensively.

[0025] The grown single crystal is processed into a disk shape, and the bonding surface is mirror-polished so that the surface roughness (Ra) is 0.5 nm or less. Although it is preferable for the bonding surface to be flat, for example, bonding is possible if the flatness is < λ / 2 (λ = 633 nm) over an area of ​​φ50 mm, and no special polishing is required.

[0026] At least one of the polished doped YAG single crystal and the polished undoped YAG single crystal is coated with a thin film containing Si by a method such as sputtering. Therefore, any of the following may be used: a thin film is coated on the bonding surface of the doped YAG single crystal, and a thin film is not coated on the bonding surface of the undoped YAG single crystal; a thin film is coated on the bonding surface of the undoped YAG single crystal, and a thin film is not coated on the bonding surface of the doped YAG single crystal; and a thin film is coated on the bonding surface of the doped YAG single crystal, and a thin film is also coated on the bonding surface of the undoped YAG single crystal.

[0027] Coating can be performed by methods other than sputtering, such as vacuum deposition and vapor phase growth. The thin film only needs to contain Si, and is preferable because Si films and Si oxide films can be formed relatively easily. Thin films that contain at least one element that becomes a divalent ion, such as Mg, Ca, Mn, or Fe, in addition to Si, are more preferable. Considering the availability of deposition materials and targets, and oxidation during heat treatment, it is preferable that these thin films are oxide thin films.

[0028] It is known that Si is effective as a sintering aid for YAG ceramics, and is thought to be effective in removing voids by activating diffusion at the bonding interface. Si is a tetravalent ion, but the Y ions and Al ions in YAG single crystals are trivalent, so by forming a thin film that contains divalent Mg, Ca, etc. at the same time as Si, it is possible to compensate for the charge, and diffusion and substitution into the YAG single crystal is further promoted, which is thought to be effective in reducing voids. The coexistence of divalent and tetravalent ions makes it possible to form the same garnet structure as YAG single crystals, and the optically inhomogeneous layer can be made as thin as possible.

[0029] Furthermore, by making the thin film an oxide containing Mg, Ca, and Si, it is possible to reduce voids. Mg diffuses relatively easily into YAG single crystals, but Ca tends to remain near the interface, as confirmed by electron microscope observation. It is believed that the presence of Ca causes Si to remain near the interface and form an amorphous phase. It is believed that the diffusion of Mg and Si into the YAG crystal and the presence of an amorphous phase near the interface reduces voids at the interface. The amorphous phase forms the same garnet phase as YAG as ion diffusion progresses during heat treatment, making it possible to thin the optically inhomogeneous layer.

[0030] In addition, since it is only necessary that an oxide thin film containing Mg, Ca, and Si is present at the joint portion of the joint of the doped YAG single crystal and the undoped YAG single crystal, there are various methods for forming such an oxide thin film. For example, there is a case where one of the surfaces of the doped YAG single crystal and the undoped YAG single crystal is coated with a thin film containing Mg, Ca, and Si in advance, and the other surface is not coated with a thin film, and then the two surfaces are joined; there is a case where one of the surfaces of the doped YAG single crystal and the undoped YAG single crystal is coated with a thin film containing Mg and Si in advance, and the other surface is coated with a thin film containing Ca and Si in advance, and then the two surfaces are joined; there is a case where one of the surfaces of the doped YAG single crystal and the undoped YAG single crystal is coated with a thin film containing Si in advance, and the other surface is coated with a thin film containing Ca and Mg in advance, and then the two surfaces are joined. As described later, the thickness of the thin film is about several tens of nm, and therefore, since a liquid phase is generated at about 1300° C. or higher, the elements will easily diffuse (even if they are not in a liquid phase). Therefore, if these elements are contained in the thin film on the surface of at least the doped YAG single crystal or the undoped YAG single crystal, an oxide thin film containing Mg, Ca, and Si will be formed at the joint between the two.

[0031] The thickness of the thin film should be from a few atomic layers to several tens of nm, with a thickness of a few nm being the most desirable. A thickness of a few nm promotes diffusion near the interface, mitigating minor irregularities and forming a good bond. A thickness thicker than a few tens of nm is not desirable because the amorphous phase remains, making the optically inhomogeneous portion thicker.

[0032] The bonding surfaces of the doped YAG single crystal and the undoped YAG single crystal are brought into close contact with each other and then heat-treated in air at 1200°C to 1600°C. Below 1200°C, the elements of the coated thin film cannot diffuse sufficiently, but at temperatures of approximately 1300°C or higher, a liquid phase is generated and diffusion is activated. Conversely, at temperatures above 1600°C, voids may grow, so high-temperature heat treatment is not necessary. During heat treatment, it is a good idea to apply a weight, such as a weight, to ensure that the bonding surfaces are in close contact with each other. High pressures such as hot pressing are not necessary; a light load of 0.1 kPa to 10 kPa is sufficient.

[0033] In this embodiment, it is more preferable to perform HIP treatment after bonding by heat treatment. By coating a thin film and then bonding, it is possible to reduce voids at the interface, but voids may remain depending on the conditions. These voids can be further reduced by HIP treatment. The conditions for HIP treatment are preferably an oxidizing atmosphere. This is because YAG will have oxygen deficiencies if treated in a reducing atmosphere, so additional oxidation treatment is necessary. Specifically, an atmosphere of Ar+O2 gas is preferable. The temperature can be 1500°C or less. A general-purpose HIP device can be used, and 1500°C is a sufficient temperature for diffusing thin film components. The pressure can be the standard conditions of the device, for example, 200 MPa.

[0034] <Example> Comparative examples and examples will be described below (see Table 1 below). The sample preparation procedure of the comparative example will be described. First, a doped YAG single crystal doped with 1 at% Nd, an optically active substance, is processed to φ50 mm × 1.5 mm and the bonding surface is mirror-polished so that the (111) plane is the bonding surface. On the other hand, an undoped YAG single crystal is processed to φ50 mm × 5 mm and the bonding surface is mirror-polished so that the (111) plane is the bonding surface. The bonding surfaces of these crystals are brought into close contact with each other and heat-treated at 1500 °C for 10 hours to prepare a bonded body. The bonded body was processed, and the fracture surface of the bonding interface was observed with a scanning electron microscope (SEM).

[0035] The sample preparation method of the examples will be described. In Examples 1 to 3, an undoped YAG single crystal was processed to 10×10×1 mm so that the (111) plane was the bonding surface, and the bonding surface was mirror-polished. The bonding surface of this undoped YAG single crystal was coated with a SiO2 film, a MgSiO3 film, and a CaSiO3 film to a thickness of about 10 nm by sputtering, as shown in Table 1. The bonding surfaces of the undoped YAG single crystals coated with the thin films were brought into close contact with each other, and heat-treated at 1500° C. for 10 hours in air to prepare a bonded body. For Examples 4 to 6, a HIP treatment was further performed in an Ar+O2 atmosphere at 1500° C. for 5 hours at a pressure of 200 MPa. The fracture surfaces of the bonding portions of these samples were observed by SEM.

[0036] [Table 1]

[0037] FIG. 1 shows an SEM photograph of the fracture surface of the bonded body of the comparative example. It can be seen that there are several small voids at the interface. FIG. 2 to FIG. 7 show SEM photographs of the fracture surface of the bonded body of the example 1 to example 6. In the example 1 and example 3, a few voids are present, but the number is greatly reduced. In the example 2 and example 4 to example 6, voids were not observed in the observation sample, or the number of voids was clearly less than that of the comparative example. It should be noted that the examples 1 to 6 are bonded bodies of undoped YAG single crystals, but even if the doped YAG single crystal is replaced with an undoped YAG single crystal, the action and effect of the thin film on the bonding surface is the same, so they are examples of this embodiment. The reason why the bonded body is composed of a doped YAG single crystal and an undoped YAG single crystal is solely for the convenience of diffusing local heat generation, and there is no difference between the doped YAG single crystal and the undoped YAG single crystal in the action and effect of coating with a thin film. Therefore, even in the case of a bonded body of a doped YAG single crystal and an undoped YAG single crystal, the same results as in Examples 1 to 6 can be obtained, and voids are naturally suppressed.

[0038] Although the embodiment of the present invention has been described in detail above, the present invention is not limited to the above embodiment, and various design modifications can be made to the present invention without departing from the scope of the claims.

Claims

1. A method for manufacturing an optical component, comprising mirror-polishing the surfaces of a doped YAG single crystal, which is an yttrium aluminum garnet single crystal doped with an optically active substance, and an undoped YAG single crystal, which is an yttrium aluminum garnet single crystal not doped with an optically active substance, coating at least one of the surfaces of the doped YAG single crystal and the undoped YAG single crystal with a thin film containing Si, and then contacting the surfaces of the doped YAG single crystal and the undoped YAG single crystal and subjecting them to a heat treatment.

2. A method for manufacturing an optical component according to claim 1, comprising the steps of: The method for producing an optical component, wherein the thin film is an oxide thin film containing an element that becomes a divalent ion.

3. A method for producing an optical component according to claim 1 or 2, comprising the steps of: A method for producing an optical component, characterized in that, by the heat treatment, a junction between the surface of the doped YAG single crystal and the surface of the doped YAG single crystal becomes an oxide thin film containing Ca and Mg.

4. A method for producing an optical component according to claim 1 or 2, comprising the steps of: In the heat treatment, the heat treatment is performed in air at 1200° C. or more and 1600° C. or less, and then O 2 2. A method for producing an optical component, comprising the steps of:

5. An optical component in which a surface of a doped YAG single crystal, which is an yttrium aluminum garnet single crystal doped with an optically active substance, and a surface of an undoped YAG single crystal, which is an yttrium aluminum garnet single crystal not doped with an optically active substance, are bonded together, an optical component comprising a thin film containing Si at a junction between said doped YAG single crystal and said undoped YAG single crystal;

6. 6. The optical component according to claim 5, wherein the thin film is an oxide thin film containing an element that becomes a divalent ion.

7. 7. The optical component according to claim 6, wherein the oxide thin film contains both Ca and Mg as the elements that become divalent ions.

Citation Information

Patent Citations

  • Composite consisting of glass-containing substance and glass-free substance, and method for forming said composite

    JP1990153849A

  • Laser resonator and solid-state laser apparatus

    JP1994275891A

  • Solid-state laser material and solid-state laser element

    JP2000101178A

  • Producing method for light amplifying thin glass film

    JP2002068779A

  • Transparent base material with antiglare antireflection film, and article

    JP2016041481A